PENILAIAN PRESTASI KERJA MENGGUNAKAN STRATEGIC MODELS SEBAGAI SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN KENAIKAN JABATAN KARYAWAN - Reina A. Hadikusumo (Jurnal Bisnis Terapan, 2018)
In organization, especially in a company, it is necessary to implement a monitoring and an appraisal toward the activities of the employees. Performance Appraisal is the activity of an organization in appraising the task that has been done by the employees / organization member. Strategic Models is one of the models in the Decision Support Systems (DSS) that can be used as an alternative way in doing the Performance Appraisal. Strategic Models is used by the top management to help in determining the organization’s objective, the resources that are needed to achieve the objective, the policy to determine the result, the usage, the assignment, and the management of the resources. In calculating formulas, Assignment Model and Sociometry Model which are used as the implementation of Strategic Models can give a useful result to the management in getting the best employee.